Severe acute malnutrition in children admitted in an Intensive Therapeutic and Feeding Centre of South Kivu, Eastern Democratic Republic of Congo: Why do our patients die? - Richard Mbusa Kambale; Gaylord Amani Ngaboyeka; Joseph Ntagerwa Ntagazibwa; Marie-Hélène Igega Bisimwa; Lisa Yvette Kasole; Viateur Habiyambere; Victor Buunda Kubuya; Joseph Kasongowa Kasongo; Emmanuel André; Dimitri Van der Linden (PLoS ONE)
Background Severe acute malnutrition (SAM) remains a serious public health concern in low- and middle-income countries. Little is known about treatment outcomes of child inpatients in Intensive Therapeutic and Feeding Units. This study aimed to assess treatment outcomes of SAM and identify factors associated with mortality among children treated at Saint Joseph Nutritional Center, South Kivu, Eastern Democratic Republic of Congo. Methods A retrospective hospital-based cross-sectional study was conducted on medical records of 633 severely malnourished children followed as inpatients at Saint Joseph Nutritional Center from July 2017 to December 2018. Data were entered, thoroughly cleaned and analyzed in SPSS version 25. Univariable and multivariable logistic regression model were fitted to identify factors associated with mortality. Results Among 633 patients admitted with SAM, 13.1% were lost to follow-up and 9.2% died while in hospital. Children with late referral to the health facility (> 14 days) after the onset of main external malnutrition signs had 2.03 times higher odds of death than those referred less than 14 days [AOR = 2.03 at 95%CI (1.12, 3.68)]. The odds of death was 1.91 times higher for children with MUAC < 115 mm than for those with MUAC ≥ 115 mm [AOR = 1.91 at 95% CI (1.05, 3.50)]. Children infected with HIV were 3.90 times more likely to die compared to their counterparts [AOR = 3.90 at 95% CI (2.80, 9.41)]. Conclusion Particular emphasis should be placed on partnering with communities to improve information on malnutrition signs and on critical importance of early referral to the health system. While HIV incidence in DRC is still low (0.21%), its impact on mortality among severely malnourished children is increased due to the limited access to HIV testing and antiretroviral therapy.